2022
DOI: 10.48550/arxiv.2203.00299
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Homogeneous Transit Timing Analyses of Ten Exoplanet Systems

Ö. Baştürk,
E. M. Esmer,
S. Yalçınkaya
et al.

Abstract: We study the transit timings of 10 exoplanets in order to investigate potential Transit Timing Variations (TTVs) in them. We model their available ground-based light curves, some presented here and others taken from the literature, and homogeneously measure the mid-transit times. We statistically compare our results with published values and find that the measurement errors agree. However, in terms of recovering the possible frequencies, homogeneous sets can be found to be more useful, of which no statisticall… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 86 publications
0
1
0
Order By: Relevance
“…Our constraint of Q ′ ⋆ > (2.76 ± 0.21) • 10 6 is tighter by a factor of ≈4. More recently, Baştürk et al (2022) have reported 3.8 • 10 6 but at a higher confidence level of 99%. For WASP-18 b, precise transit timing observations span over 13 years, making the system the most sensitive probe in the tidal dissipation studies.…”
Section: Discussionmentioning
confidence: 92%
“…Our constraint of Q ′ ⋆ > (2.76 ± 0.21) • 10 6 is tighter by a factor of ≈4. More recently, Baştürk et al (2022) have reported 3.8 • 10 6 but at a higher confidence level of 99%. For WASP-18 b, precise transit timing observations span over 13 years, making the system the most sensitive probe in the tidal dissipation studies.…”
Section: Discussionmentioning
confidence: 92%